Peer review of the pesticide risk assessment of the active substance garlic extract. (5th June 2020) - ,; Anastassiadou, Maria; Arena, Maria; Auteri, Domenica; Brancato, Alba; Bura, Laszlo; Carrasco Cabrera, Luis; Chaideftou, Eugenia; Chiusolo, Arianna; Marques, Daniele Court; Crivellente, Federica; De Lentdecker, Chloe; et al.
Abstract: The conclusions of the EFSA following the peer review of the initial risk assessments carried out by the competent authorities of the rapporteur Member State, Ireland, and co‐rapporteur Member State, Denmark, for the pesticide active substance garlic extract and the considerations as regards the inclusion of the substance in Annex IV of Regulation (EC) No 396/2005 are reported. The context of the peer review was that required by Commission Implementing Regulation (EU) No 844/2012, as amended by Commission Implementing Regulation (EU) No 2018/1659. The conclusions were reached on the basis of the evaluation of the representative use of garlic extract as a repellent, insecticide and nematicide on a wide range of crops in agriculture, horticulture, amenity. The reliable end points, appropriate for use in regulatory risk assessment are presented. Missing information identified as being required by the regulatory framework is listed. Concerns are identified.